Richard Easterlin, Population, Labor Force and Long Swings in Economic Growth. The American Experience. National Bureau of Economic Research no. 86, General Series. Nueva York, Columbia University Press, 1968. 298 p. - Alejo, Francisco Javier (Estudios Demográficos y Urbanos, 1970)
RICHARD EASTERLIN, Population, Labor Forcé and Long Swings in Economic Growth. The American Experience. National Bureau of Economic Research, Núm. 86, General Series. Nueva York, Columbia University Press, 1968.